Analysis of Processing and Income of Nutmeg Products at Home Industry Fala Tanawan in Maliaro Village, Central Ternate City - Anwar, Gian Nofita; Lakamisi, Haryati; Muhammad, Munawir; Ekaria, Ekaria; Marsaoly, Hasrul (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to determine the nutmeg processing process and analyze income from processing nutmeg products at the Fala Tanawan Home Industry in Maliaro Village, Central Ternate District. The method used in this research is a quantitative descriptive analysis method which includes production costs, receipts and income. The results of this research are the nutmeg production process at the Fala Tanawan Home Industry in Maliaro Village, Central Ternate City, which starts from the nutmeg ripening process until entering the packaging stage. This aims to increase the selling value of nutmeg so that 4 products can be created, including nutmeg syrup. , bebidas reis, crunchy nutmeg and nutmeg juice. The income from the nutmeg processing business is the difference between the total revenue received and the total production costs incurred. The income of the Fala Tawan Home Industry, Maliaro Village, Central Ternate City, from all the processed nutmeg products produced, namely total income from nutmeg syrup amounting to Rp. 12,172,779, bebidas reis amounting to Rp. 1,967,779, crispy nutmeg amounting to Rp. 7,099,779 and total income from nutmeg juice products amounting to 2,017,779. In accordance with the income from the processed products produced, the income level is still relatively high, even though these products are not routinely produced at the Fala Tawan Home Industry.